Tracking fertilizer price volatility: Expanding the Food Security Portal’s excessive food price variability early warning system - Hernandez, Manuel A.; Yao, Feng; Kim, Soonho (International Food Policy Research Institute, 2025)
Fertilizer is a critical input for agricultural productivity, and its increased use has been closely associated with rising agricultural yields in many countries. In developing economies that rely heavily on fertilizer imports and are home to vulnerable smallholder farmers, fertilizer price spikes can pose serious risks. When farmers lack access to effective risk-sharing mechanisms, sudden or excessive increases in fertilizer prices can discourage adoption, disrupt planting decisions, and reduce productivity.